The Effect of Organizational Culture and Work Dicipline on Employee Job Satisfaction (A Case Study at Pramana Watu Kurung Hotel Bali) - Vica Harum Widyanti; Khoirur Rozaq (Lavish Opulent Education, 2026)
This study aims to examine the effect of organizational culture and work discipline on employee job satisfaction at Pramana Watu Kurung Hotel Bali. This research employed a quantitative approach using a survey method involving 48 respondents who were all employees of the hotel. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression with IBM SPSS Statistics version 26. The descriptive results indicate that organizational culture and work discipline are categorized as high, while job satisfaction is categorized as moderate. Partial test results show that organizational culture has a positive and significant effect on job satisfaction and work discipline also has a positive and significant effect on job satisfaction. Simultaneously, both variables significantly affect job satisfaction with an adjusted R² value of 0.445, indicating that 44.5% of job satisfaction variation is explained by organizational culture and work discipline, while the remaining is influenced by other variables outside this study.